Aeternum Dei servitium ad sanctum locum. Pokuta zabójców Pięciu Braci Męczenników w relacji Brunona z Kwerfurtu - Kotecki, Radosław (Kwartalnik Historyczny, 2014)
Aeternum Dei servitium ad sanctum locum. The Penance of the Murderers of Five Martyred Brethren in an Account by Bruno of Querfurt This article is a first attempt at systematically considering the penance imposed by Bolesław the Brave on the assassins of the so-called Five Martyred Brethren, described in Vita Quinquae Fratrum Eremitarum by St. Bruno of Querfurt (BHL 1147). The killers of the hermits were condemned to life-long penance in an abbey founded by Duke Bolesław on the site of the desecrated hermitage soon after the crime (about 1003–1006). The posed research questions concern, predominantly, the reasons for this particular penance, its purpose and character, as well as sources and cultural context in the form of the tradition of monastic penance (Klosterbuße). The conducted analysis leads to a conclusion claiming that putting murderers in monastery was the result of a carefully planned decision of the Polish ruler, taking into consideration a number of the factors, including legal requirements. Comparative survey made it possible to find many significant West European analogies to the penance imposed on murderers of Five Martyred Brethern both in normative sources (capitularies, penitentials, canon law collections, synodal statutes) and those referring to the penitentiary practice of the early Middle Ages. Their confrontation with the account by Bruno of Querfurt demonstrates that the solution accepted by Bolesław the Brave took into consideration regulations known from penitential or canonical tradition condemning the killers of clergymen to life-long penance in a monastery known from the seventh century as servitium Dei. Following their contents, the duke resigned from his original intention to incarcerate the felons in ducal prison or to sentence them to death in favour of chastisement corresponding to standards that should be respected by a Christian ruler. The penalty did not deprive the perpetrators of the perspec tive of salvation. The proposed analysis casts a new light not only on the issue of penitential practice during the Early Piast era but also on the wider problem of the application of regulations borrowed from Western culture in the domain ruled by Bolesław the Brave. The article expands heretofore knowledge about the part performed by Duke Bolesław in binding his state with the circle of post-Carolingian Latin civilisation through a conscious acculturation of Christian customs and norms.